Development of Islamic thought in China : a study of the views of Ismail Zhang Cheng Qian - Yin, Zainab Zhiming (Kulliyyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This research is a study about the development of Islamic thought in China. The researcher mainly selects the modern Muslim intellectual Ismaīl Zhang Cheng Qian as the subject of the study and explores his thought expressed in his works. The researcher achieved the aims of study based on an investigation of Ismaīl Zhang's intellectual background, and elaboration of his controversial views between traditional Muslim scholars and modernist intellectuals, especially on revelation (wahy), the unseen world (ālam al-ghayb) and miracles (mu'jizāt) since his interpretations are different from the orthodox Islamic perspective, as presented in his two works; The Call of Islam (1992) and Chinese Translation and Commentary of Qurʼān (2005). In addition, the influence of Ismaīl Zhang's thought on Sino-Muslim was presented, by collecting and analyzing readers' letters, book reviews, and Ismaīl Zhang's own accounts in interviews by e-mails. There are supporters who donated funds to help him publish his works and spread his thought in China. The researcher puts them into different categories according to their identity characteristic; namely, his followers, educated Muslims and new Muslims. Based on previous studies, the researcher finally recommended some suggestions for further direction and the emphasis on the study of Ismaīl Zhang's works and thought.